Conservation of ptfA gene encoded Type IV fimbrial protein among circulating Pasteurella multocida serogroup A strains causing pneumonia in sheep - PRAJAPATI, A; CHANDA, M M; YOGISHARADHYA, R; PARVEEN, A; UMMER, J; DHAYALAN, A; MOHANTY, N N; SHIVACHANDRA, S B (The Indian Journal of Animal Sciences, 2021)
Respiratory infections are most common in small ruminants. Differentiation of homogenous bacterial strains originated from similar clinical forms (acute or chronic) of infections in a particular or diverse host origin and regions posses a greater challenge for rapid epidemiological studies. Pasteurella multocida, being a multi-host pathogen with wide range of infections among small ruminants especially sheep, is of greater economical concern among small and marginal farmers. In our study, we report ptfA gene sequence based analysis of circulating P. multocida strains recovered from clinically ailing sheep either with pneumonia or septicaemia belonging to different geographical regions of Karnataka. All the 29 P. multocida strains were characterized by conventional methods as well as molecular methods which indicated homogeneity as they belonged to serogroup A and possessed highly conserved ptfA gene by phylogenetic analysis. The study highlighted the conservation of ptfA gene/fimbrial protein among P. multocida strains from identical/diverse clinical conditions and could be employed in rapid epidemiological studies in routine surveillance of circulating pathogenic bacterial strains as well as pasteurellosis outbreak investigations among animals and birds.